Analisis Strategi Bisnis Pada Ukm Xyz Dengan Menggunakan Internal Dan Eksternal Factor Evaluation Matrix - Ayumi Dwi Lestari; Thiara Aurellya Abean; Dina Fariha Insani; Nayla Azmi Pradita; Luthfi Azmi Lubis (Journal of Management and Creative Business, 2024)
Small and medium enterprises (SMEs) play a significant role in the Indonesian economy. The beverage industry, especially the contemporary tea drink which is increasingly popular among the public, is one of the SME sectors that is growing rapidly. UKM XYZ is a tea beverage business originating from Bogor. UKM XYZ offers original tea variants and also 16 other flavor variants. Currently, UKM XYZ employs 23 multifunctional employees. To remain competitive and develop amidst increasingly fierce competition and changing market dynamics, SME XYZ needs to have a strong business strategy. Therefore, business strategy analysis is very important. The method used in this research is SWOT Analysis with Internal Factor Evaluation (IFE) and External Factor Evaluation (EFE) Matrix. Based on the calculations that have been carried out, SME XYZ is located in quadrant I with an IFE value of 3.44 and an EFE of 3.01. So the right open growth strategy for SME XYZ is to carry out product development which involves developing new products for the market.